Tactics in counselling patients to start insulin - Lee, Y.K.; Lee, P.Y.; Ng, C.J. (2013)
Fifty-one per cent of patients with Type 2 diabetes in Malaysia are reluctant to take insulin 1. Patient education plays an important role in facilitating insulin initiation. In Malaysia, patient education material on insulin is lacking and patient education delivery relies on individual healthcare professionals. Our study aimed to explore the views of healthcare professionals on the content and delivery of patient education on insulin initiation. This study was part of a larger 3-year study aimed at developing a decision support tool for insulin therapy.